Activation and formation of creative potential of students-medics - Slukhenska, Ruslana; Tsurkan, Ivan (Journal of Education, Health and Sport, 2019)
The need of activation of creative potential of future doctors is increased during their studying at HEI, under the conditions of the market economy, when provision of medical service becomes an area of high professional competence and new requirements are put forward towards doctor’s personality. The problem of activation a formation of creative potential of students-medics is considered in the article. The development of structurally-functional model and theoretical grounding of pedagogical conditions of formation of creative potential of future doctors during studying at higher educational institution are aim of the article.